Burkina Faso: Shipping around the Malthusian trap - Michael Grimm; Claude Wetta; Aude Nikiema (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Burkina Faso has experienced quite significant aggregate growth over the past two decades, but that growth has not been transformed into poverty reduction. The key obstacles preventing large-scale escape from poverty are very high population growth combined with the absence of major technological change in agriculture and any significant structural transformation of the urban economy. Continuously rising food prices and droughts maintain child malnutrition and mortality at high levels, threatening the political and social stability of the country. Dealing with Malthusian forces is the main challenge for Burkina Faso in the decade to come.
Keywords: I32; O5; O33; Q11; 330; Burkina Faso; food crisis; inequality; poverty; Malthusian Trap; structural change